The Impact of Gamification on Creating Fun and Interactive Learning Processes - Andromeda Valentino Sinaga; Rimma Sianipar (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
This study aims to examine the impact of implementing gamification on creating fun and interactive learning processes among students at Universitas Negeri Makassar. The research employed a one-group pretest–posttest design involving 42 students. Data were collected through tests, Likert-scale questionnaires, and observation sheets. The results indicate an improvement in students’ average scores, increasing from 64.3 in the pretest to 81.6 in the posttest. In addition, 95.2% of the students reported that gamification-based learning was engaging, while observational data revealed higher levels of active participation, enthusiasm, and interaction throughout the learning process. These findings suggest that gamification has the potential to enhance the quality of learning by fostering a more interactive and meaningful learning environment in higher education.